CORRELATION BETWEEN PHYSICAL ACTIVITY AND COGNITIVE FUNCTION AMONG THE ELDERLY AT PADANG KANDIS PUBLIC HEALTH CENTER - Zakiya Zulviyanda; Fika Tri Anggraini; Tofrizal Tofrizal (Medika Kartika : Jurnal Kedokteran dan Kesehatan, 2026)
The increasing global elderly population has been accompanied by a rise in age-related health problems, particularly degenerative conditions such as cognitive decline. Physical activity is considered a modifiable factor that may play a protective role in maintaining cognitive health, as regular exercise is believed to delay cognitive deterioration in older adults. This study aimed to investigate the correlation between physical activity and cognitive function among elderly individuals living within the service area of Padang Kandis Public Health Center, located in Lima Puluh Kota Regency. This study employed an analytic observational design with a cross-sectional approach. Participants were selected using a consecutive sampling technique, resulting in 52 elderly individuals residing in the study area. Physical activity levels were assessed using the Global Physical Activity Questionnaire (GPAQ), while cognitive performance was evaluated using the Indonesian version of the Montreal Cognitive Assessment (MoCA-Ina). Bivariate analysis was performed using the chi-square test. The results showed that 23 respondents (44.23%) engaged in a moderate level of physical activity, and 27 respondents (51.92%) demonstrated normal cognitive function. Statistical analysis indicated a significant relationship between physical activity and cognitive function, with a p-value of 0.001 (p < 0.05). In conclusion, this study demonstrated a significant association between physical activity levels and cognitive performance in the elderly population served by the Padang Kandis Public Health Center. Keywords: cognitive function, elderly, GPAQ, MoCA-Ina, physical activity DOI : 10.35990/mk.v9n1.p57-67